CARDIOTROPIC INFLUENCE OF SYNTHETIC AND GENETICALLY-ENGINEERED SUPPRESSORS IN RATS WITH EXPERIMENTAL RHEUMATOID ARTHRITIS COMBINED WITH ARTERIAL HYPERTENSION - Seredynska, N.M.; Korniyenko, V.I.; Marchenko-Tolsta, K.S.; Bobrytska, O.M.; Ladohubets, O.V.; Duchenko, K.A. (World of Medicine and Biology, 2020)
Significant progress in rheumatoid arthritis pharmacotherapy is associated with the implementation of synthetic–derived immunosuppressors and genetically engineered (biological) drugs) into clinical practice. Arterial hypertension, like rheumatoid arthritis, is accompanied by producing a large amount of inflammatory cytokines, namely TNF–ά. The purpose of the work was to study the cardiotropic effects of leflunomide and etanercept against the background of experimental rheumatoid arthritis associated with arterial hypertension in rats. Experiments on mature adult, non-linear white rats found that leflunomide and etanercept did not affect the degree of hypertension against the background of adjuvant arthritis, but manifested an antihypertensive effect when used in adjuvant arthritis combined with arterial hypertension. Leflunomide leads to an increase in heart rate by 5–10.4% at different terms of observation, both against the background of adjuvant arthritis only and under the combined pathology conditions. Etanercept, when used against adjuvant arthritis, causes bradycardia but prevents the development of tachycardia, which is detected in untreated animals with a comorbid condition during manifestation and attenuation of the inflammatory process. The study findings may be relevant for development of new approaches to the treatment of rheumatic and cardiac pathology.
Keywords: leflunomide; etanercept; cardiotropic action; rheumatoid arthritis; hypertension; comorbid pathology